Production and Characterization of α-Amylase from an Extremely Halophilic Archaeon, Haloferax sp. HA10 - Bhakti Bajpai; Monika Chaudhary; Jyoti Saxena (Food Technology and Biotechnology, 2015)
Haloarchaea are found at very high concentrations in salt-conditioned environments, hence produce enzymes which are able to catalyze reactions under harsh conditions, typical of many industrial processes. In the present study, culture conditions for extracellular amylase production from Haloarchaea isolated from a solar saltern were optimized and the purified enzyme was characterized. Haloferax sp. HA10 showed maximum amylase production at 3 M NaCl, 37 °C, pH=7 and 1 % starch content. Purified α-amylase was a calcium-dependent enzyme with an estimated molecular mass of about 66 kDa and many industrially useful properties. It was found to be stable in a broad range of pH (from 5 to 9) and NaCl concentrations (from 0.5 to 3.0 M), retaining 48 % activity even at 4 M. The optimal temperature for Haloferax sp. HA10 amylase activity was 55 °C (99 % activity), and 57 % activity was retained at 80 °C, which dropped to 44 % with the increase of temperature to 90 or 100 °C. It was able to sustain various surfactants and detergents. To the best of our knowledge the detergent-stable α-amylases from halophilic archaeon have not been reported yet.